Retrospective pharmacoeconomic study of antibiotic therapy in community-acquired pneumonia - A. A. Taube; T. V. Alexandrova; O. A. Demidova; M. V. Zhuravleva (IRBIS LLC, 2023)
Background. The global recommendations for the treatment strategy of community-acquired pneumonia (CAP) include the empirical prescription of antibiotic therapy (ABT) - beta-lactams, fluoroquinolones, macrolides until the results of laboratory tests are obtained to identify the etiological agent responsible for CAP to determine etiotropic therapy. According to the national Russian clinical guidelines, macrolides, fluoroquinolones, cephalosporins and aminopenicillins are recommended for empirical prescription. Meta-analyses found better outcomes in patients treated with a combination of macrolides with beta-lactam compared to beta-lactam alone. At the same time, the clinical benefit of adding macrolides to beta-lactams for the empirical treatment of moderate CAP remains controversial, since the difference in the results of therapy may depend on the age and comorbid conditions of patients.Objective: to analyze the costs of treating CAP with various ABT strategies in order to optimize the cost structure of a medical organization and plan the budget of local healthcare systems.Material and methods. A retrospective epidemiological analysis of extracts from 157 medical records of middle-aged patients in accordance with the World Health Organization classification treated in multidisciplinary medical organizations was carried out. The methods included frequency analysis, cost of illness analysis, cost minimization analysis, and cost-effectiveness analysis. Depth of research was 2 years.Results. Frequency analysis revealed that the initial strategy of ceftriaxone and azithromycin combination (n=74; 47%) prevailed in prescriptions. In terms of the rate of prescriptions, ceftriaxone monotherapy (n=37; 24%) was in the second place. The analysis of the effectiveness of the selected ABT strategies showed that, in general, 113 (72%) of prescriptions were effective. Standard therapy strategies were equivalent in absolute costs and had a similar cost structure.Conclusion. Doctors' adherence to national clinical guidelines for CAP treatment was found when prescribing the initial empirical ABT, the dominant strategies were identified. Cost of illness analysis demonstrated that the applied strategies were optimal in terms of cost minimization, and cost-effectiveness ratio. The costs structure in therapy with various ABT strategies did not have significant differences. In medical organizations, they adhere to the most rational and cost-effective strategy for CAP treatment and prescribe ABT regimens in each individual case based on risk factors, as well as the results of studies of CAP pathogens sensitivity.